Lost paradise : Symbolist Europe. - Théberge, Pierre; Clair, Jean (Montreal : Montreal Museum of Fine Arts, 1995)
Catalog of the exhibition "Lost Paradise: Symbolist in Europe" held June 8-Oct. 15, 1995 at the Montreal Museum of Fine Arts.
Engels
Lost paradise. Symbolist Europe [Montreal]
kunstcatalogus
Keywords: Symbolisme; Europa